A Scoping Review of Economic Evaluations of Workplace Wellness Programs. (November 2021) - Unsal, Nilay; Weaver, GracieLee; Bray, Jeremy; Bibeau, Daniel
Objective: Debates about the effectiveness of workplace wellness programs (WWPs) call for a review of the evidence for return on investment (ROI) of WWPs. We examined literature on the heterogeneity in methods used in the ROI of WWPs to show how this heterogeneity may affect conclusions and inferences about ROI. Methods: We conducted a scoping review using systematic review methods and adhered to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. We reviewed PubMed, EconLit, Proquest Central, and Scopus databases for published articles. We included articles that (1) were published before December 20, 2019, when our last search was conducted, and (2) met our inclusion criteria that were based on target population, target intervention, evaluation method, and ROI as the main outcome. Results: We identified 47 peer-reviewed articles from the selected databases that met our inclusion criteria. We explored the effect of study characteristics on ROI estimates. Thirty-one articles had ROI measures. Studies with costs of presenteeism had the lowest ROI estimates compared with other cost combinations associated with health care and absenteeism. Studies with components of disease management produced higher ROI than programs with components of wellness. We found a positive relationship between ROI and program length and a negative relationship between ROI and conflict of interest. Evaluations in small companies (≤500 employees) were associated with lower ROI estimates than evaluations in large companies (>500 employees). Studies with lower reporting quality scores, including studies that were missing information on statistical inference, had lower ROI estimates. Higher methodologic quality was associated with lower ROI estimates. Conclusion: This review provides recommendations that can improve the methodologic quality of studies to validate the ROI and public health effects of WWPs.